KERETA SINGO BARONG DI KERATON KASEPUHAN CIREBON - ., Sumino (CORAK, 2012)
This study to look at the changes the meaning of Singo Barong in the context of the past as understood by the public Cirebon in the present. In the time, the train experienced a period of transit which to change the context in which the material or object of art will have meaning. As a result of the frequent occurrence of changes in the context of the meanings are often subject to change. It is an art object in transition, experiencing a change of meaning as a result of changes in context. Change of meaning will evoke an emotional response when crossing cultural boundaries. Reading of documents or artifacts that are relevant necessary to achieve a deeper meaning and detail. Therefore anthropological perspective that links production and consumption of artifacts are not separated from the question of the culture, politics, religion and others. Borrowing the theory of "processual relativism" Svasek will bring an understanding of the art material in a different time and space. At least not with borrowed this theory will be obtained the values ââbehind the train characteristics. By finding the characteristics at a certain time and space will be acquired meaning, then what meaning it will be reviewed and compared. Such way of thinking is more easy to see the socio-cultural change at both the pattern of thought or social institutions Kasepuhan Cirebon palace. Singo Barong train its existence is equivalent to other objects stored in the Museum Kasepuhan Cirebon, such as gamelan, batik cloth, weapons, and so forth. Artifacts have the same weight value when used as a tool in the ritual. But the context has a different meaning, is associated with the constituent. From time to time, the meaning is changed, both in social and cultural areas. Religious meaning at the time of the kings was in power changed the fulfillment of the ritual or ceremonial, then change as the fulfillment of the economy and tourism. Keywords: Train Singo Barong, Svasek, Changes